Early β-blocker use and in-hospital outcomes in patients with chronic obstructive pulmonary disease hospitalized with acute coronary syndrome: findings from the CCC-ACS project - Zhang, Tao; Wang, Xu; Zhang, Yucheng; Feng, Tingting; Zhou, Yujie; Zhao, Lin (Frontiers in Cardiovascular Medicine, 2024)
Background: Patients with chronic obstructive pulmonary disease (COPD) after acute coronary artery syndrome (ACS) are at increased risk of heart failure and death. However, β-blocker was underused in this population group due to concerns of adverse reactions.The aim of this study is to investigated β-blocker prescription at admission and it's impact on in-hospital outcomes in patients with COPD after ACS in a Chinese national cohort.Methods: Among 184 850 patients with ACS enrolled between November 2014 to July 2019 in the national registry of the Improving Care for Cardiovascular Disease in China. 1084 ACS patients with COPD were included in this study. The primary endpoint was in-hospital mortality.The secondary endpoint was the composite of in-hospital all-cause death and heart failure.Results: Early oral β-blocker therapy was administered to 49.8% of patients. Kaplan-Meier analysis showed that early β-blocker treatment group had lower all-cause mortality (0.9% vs 2.9 %; P<0.05) and lower combined endpoint events rate (8.2% vs 12.0%; P<0.05), as compared to non-early β-blocker treatment group. Inverse-probability-of-treatment weighting analysis showed that early β-blocker treatment group was associated with significantly reduced incidence of all-cause death (risk ratio: 0.332, 0.119 -0.923, P = 0.035), heart failure (risk ratio: 0.625, 95% CI: 0.414 -0.943, P=0.025) and combined endpoint events (risk ratio: 0.616, 95% CI: 0.418-0.908, P = 0.014), respectively. In the subgroup of patients over 70 years of age, the corresponding hazard ratio was 0.268 (95% CI 0.077 to 0.938) for all-mortality and 0.504 (95% CI 0.316 to 0.805) for combined endpoint events.β-blocker was underused in patients with COPD and ACS in China. Early β-blocker therapy is associated with an improvement of in-hospital outcomes in patients with COPD after ACS. Keywords β-blocker; chronic obstructive pulmonary disease (COPD); acute coronary artery syndrome (ACS); in-hospital outcomes; early use.